La preposizione su e alcuni suoi corrispettivi polacchi – uno studio cognitivo - Malinowska, Maria (Kwartalnik Neofilologiczny, 2020)
The analysis of the Italian preposition su in spatial contexts (static, involving undirectional movement or dynamic) leads to the conclusion that su engenders support and contiguity schema interpretation in whatever context it appears. The term support implies terms such as surface and contiguity (contact). In both static and dynamic contexts the location of a trajector is visualized as contigously situated on the surface of the landmark. In both cases the landmark is an idealized plane whose boundaries are perceptively unimportant in a given configuration, even though in the real world they are clearly cut. The boundaries, which are not focalized, render possible the temporal uses of the unit su with the meaning of an approximate location in time. The Polish equivalents of su phrases are the following: na+loc, na+acc, po+loc, około(koło)+gen. The structures na+loc, na+acc involve the support and contiguity schema. The construction około(koło) +gen can be analyzed with near – far schema and applies to the approximate location in space and time in Polish. The schematic meaning is conveyed not only by prepositional units but also by inflectional case governed by prepositions. Usually such a case is convergent with dynamic (accusative) or static (locative, genitive) predication.
Keywords: image schemas: contiguity and support; embodiment; inflectional case semantics; localist theory of case